Design and development of carnival games - Lee, Calista Chu Wei (Nanyang Technological University, 2020)
In recent years, technology has been advancing rapidly with the development revolves around inventions and innovations. The main objective of this project is to incorporate technology, to increase awareness and interest in Electrical and Electronics Engineering to the younger generation. This is done by creating, designing and building a carnival game and at the same time applying knowledge of what we have learnt from this course. In this project, we aim to create and build a shooting carnival game which brings fun and enjoyment to the players and at the same time spark their interest in engineering knowledge. A Seeeduino Nano Board that uses the Atmega328P -- 8 bit AVR microcontroller will be used as the controller for shooting star. The main frame will be built with 38cmx50cm base wood profile, completed with two shooting board frames standing at 15cm and 30cm respectively . A few vibration sensors will be used to detect hitting. A full scale functional form designed will be constructed. The game includes different difficulty levels suitable for children , students , working adults and elderly .